D8.3 Report on Regional Exploitation platform - Neophytides, Stelios; Themistocleous, Kyriacos; Kaskara, Mariza; Alatza, Stavroula (My University, 2022)
This report aims to overview the possibility of the establishment of a Regional Exploitation platform that would provide the technical means to foster the use of purposive inflows and outflows of knowledge that can be used to accelerate internal innovation and expand the markets for external use of innovation. The main objective of this deliverable is to provide an overview of the EO platforms market, identify the current needs of remote sensing users and developers and examine how ECoE’s EO services can be implemented. An important aspect of this report and deliverable is to examine how a Digital Innovation Hub can benefit from developing a regional exploitation platform. Based on this extensive overview provided in this deliverable, there are a plethora of the existing EO online platforms in the market. The need to establish a new platform similar to other available platforms will be examined as the EXCELSIOR project evolves. Therefore, an efficient method to fully exploit the potential of ECoE’s research fields and serve the remote sensing community and the public in general would be to make it available through such a platform. The detection of existing or even future needs in remote sensing society, the integration of ECoE’s services to the EO market and the effective use of ECoE’s products in existing online platforms for research, institutional or even governmental activities are of primary importance for ECoE’s further development and recognition. The evolution of EO online platforms continued to further improve data management and ease user access and exploitation capacities. During the next few years, ECoE will continuously examine the capabilities of these platforms in order to take full advantage of the technological advances in the industry of creating or using such platforms.
Keywords: Remote Sensing; EXCELSIOR; ERATOSTHENES Centre of Excellence; Earth Observation; Digital Innovation Hub